2021
DOI: 10.3390/ijms222413321
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Exposure Promotes Commensal-to-Pathogen Transition in Pseudomonas aeruginosa Leading to Mucosal Inflammation and Illness in Mice

Abstract: The opportunistic pathogen Pseudomonas aeruginosa (P. aeruginosa) is associated gastrointestinal (GI) inflammation and illness; however, factors motivating commensal-to-pathogen transition are unclear. Excessive zinc intake from supplements is common in humans. Due to the fact that zinc exposure enhances P. aeruginosa colonization in vitro, we hypothesized zinc exposure broadly activates virulence mechanisms, leading to inflammation and illness. P. aeruginosa was treated with excess zinc and growth, expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Past analyses of leachate from this specific PVC plastic showed it is comprised of a complex mix of both organic and inorganic substances, with levels of zinc, a common PVC additive, found to be particularly high (Tetu et al, 2019). As Zn exposure has previously been shown to increase the prevalence of antibiotic resistant bacteria in the environment (e.g., Poole, 2017; Silva et al, 2021), and promote virulence in host-associated bacteria (Wu et al, 2021), we also looked to see if exposure to zinc alone was sufficient to account for the PVC leachate impact on AMR and virulence gene prevalence. Using PathoFact predictions, we found that treatment with two concentrations of zinc, ZnL (0.13 mg/L ZnCl) and ZnH (1.3 mg/mL ZnC1), had no effect on the relative abundance of AMR, virulence or toxicity genes compared to untreated seawater controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Past analyses of leachate from this specific PVC plastic showed it is comprised of a complex mix of both organic and inorganic substances, with levels of zinc, a common PVC additive, found to be particularly high (Tetu et al, 2019). As Zn exposure has previously been shown to increase the prevalence of antibiotic resistant bacteria in the environment (e.g., Poole, 2017; Silva et al, 2021), and promote virulence in host-associated bacteria (Wu et al, 2021), we also looked to see if exposure to zinc alone was sufficient to account for the PVC leachate impact on AMR and virulence gene prevalence. Using PathoFact predictions, we found that treatment with two concentrations of zinc, ZnL (0.13 mg/L ZnCl) and ZnH (1.3 mg/mL ZnC1), had no effect on the relative abundance of AMR, virulence or toxicity genes compared to untreated seawater controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Falling under the resistant nodule (RND) super-family of heavy metal efflux (HME) proteins, this complex has gained much attention due to its impressive abilities. Cupriavidus metallidurans, a bacterium revered for its resilience against heavy metals, was the first organism to uncover the secrets behind this pump [38]. The role of the membrane fusion protein CzcB is paramount in creating a loop that solidifies the bond between CzcA and CzcC.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the reduced concentration of zinc in livestock feeding, many studies have reported that the presence of a very low metal, antibiotic, or biocide concentration plays an essential role in the selection, proliferation, and maintenance of existing resistant mutants ( 11 – 14 ). Furthermore, a long-term exposure of bacteria to sub-lethal doses of environmental pollutants may lead to the evolution, horizontal transfer, and spread of antimicrobial resistance genes ( 11 ) as well as increased prevalence and spread of virulence traits ( 15 ). Cellular changes at the genomic, transcriptomic, and proteomic level can be manifested in the bacterial phenotype, which can then significantly disturb the balance of the microbiome, including that of the mammalian gastro-intestinal tract ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a long-term exposure of bacteria to sub-lethal doses of environmental pollutants may lead to the evolution, horizontal transfer, and spread of antimicrobial resistance genes ( 11 ) as well as increased prevalence and spread of virulence traits ( 15 ). Cellular changes at the genomic, transcriptomic, and proteomic level can be manifested in the bacterial phenotype, which can then significantly disturb the balance of the microbiome, including that of the mammalian gastro-intestinal tract ( 15 ). It is known that mutations in genes involved in transcription and translation, structural genes, and those in membrane transport are behind the mechanism of metal-induced resistance to antibiotics ( 16 ).…”
Section: Introductionmentioning
confidence: 99%